2010
DOI: 10.1089/dna.2010.1034
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Polymorphisms at Small Ubiquitin-Like Modifier 1 and Nonsyndromic Orofacial Clefts in Western China

Abstract: Small ubiquitin-like modifier 1 (SUMO1) has been shown to be associated with cleft lip and palate in animal models. However, rarely studies have linked SUMO1 to nonsyndromic cleft lip with or without cleft palate in humans. The purpose of this study was to confirm the contribution of SUMO1 to nonsyndromic orofacial clefts in western Han Chinese. Four single-nucleotide polymorphisms were investigated in 246 case trios in western China using conditional logistic regression, transmission disequilibrium test, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Several studies [5], [48] have shown associations between gene variations in SUMO1 and NSCL/P. Jia et al reported that the C allele in rs7580433 is overtransmitted from parents to affected individuals in west China [49]. However, we did not observe an association between rs7580433 in SUMO1 and cases and controls (p = 0.561).…”
Section: Discussioncontrasting
confidence: 86%
“…Several studies [5], [48] have shown associations between gene variations in SUMO1 and NSCL/P. Jia et al reported that the C allele in rs7580433 is overtransmitted from parents to affected individuals in west China [49]. However, we did not observe an association between rs7580433 in SUMO1 and cases and controls (p = 0.561).…”
Section: Discussioncontrasting
confidence: 86%
“…The reference numbers for those represented in dbSNP are given in Table 1. Because several previous reports have indicated association between SUMO1 and clefting (Song et al,2008; Carter et al,2010; Jia et al,2010), we compared the allele distribution of the identified SNPs (with MAF values above 5%) between patients with CLP and controls. All SNPs were found to follow Hardy–Weinberg equilibrium but no alleles were demonstrated to support a statistical association with the cleft cohort under study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In mouse, SUMO1 was found not only to be expressed in the lip and primary palate during embryonic development but also a heterozygous SUMO1 gene‐trap model was reported to have CP at a low penetrance (Alkuraya et al,2006). Subsequently, several studies have demonstrated evidence of association between CLP and SUMO1 (Song et al,2008; Carter et al,2010; Jia et al,2010; Mostowska et al,2010; Jia et al,2011) or with deletion of the SUMO1 locus (Shi et al,2009). Sumoylation has also been demonstrated to be an important functional modification for several transcription factors that are known to play important roles in lip and palate development, including MSX1, SATB2, TBX22, and TP63 (Huang et al,2004; Dobreva et al,2006; Gupta and Bei,2006; Andreou et al,2007).…”
Section: Introductionmentioning
confidence: 99%
“…Second, a 4-SNP SUMO1 haplotype was found significantly associated with non-syndromic cleft lip with or without cleft palate (NSCLP) from a study of 181 patients and 162 healthy controls of Han Chinese origin [ 114 ]. Other studies have also related SUMO1 to cleft lip with or without cleft palate, cleft palate only, or NSCLP in Poland [ 115 ], Ireland [ 116 ], and western China [ 117 ] ( Figure 3 B). In addition, transcription factors such as TBX22, MSX1, SATB2, P63, PAX9, TRPS1, and EYA1, which contribute to the development of the lip and palate, have all been identified as substrates of SUMO modification [ 118 ].…”
Section: Sumoylation In Skeletal Cell Differentiation Homeostasis And...mentioning
confidence: 99%